EFFECTS OF PHOSPHATE SOLUBILIZERS AND BIOCHAR ON GROWTH AND YIELD OF TOMATO (SOLANUM LYCOPERSICUM) - Mutalib, Asilah Abdul (Journal of Vocational Education Studies, 2019)
A study was conducted to determine the effects of phosphate solubilizers and biochar on growth and yield of tomato plants. For this purpose, a 4×3 factorial experiment based on Completely Randomized Block Design (RCBD) with 4 replications were conducted in the growth room. In this factorial experiment, 4 levels of phosphate solubilizer bacteria (B1, B2, Bmix and Control) and 3 levels of biochar (Powder, Large Size, and Control) were applied on tomato plants to identify changes in growth parameters and yield. Results were analysed using Genstat Statistical Package (16th Edition). Analysis of Variance (ANOVA) were conducted to test the effects of each factor and their interactions. Subsequently, Tukey test was used to compare the treatments means at P<0.05. The results showed that phosphate solubilizers had no significant effects on the growth parameters measured, while biochar treatments significantly affected the total fresh weight of the tomatoes and increased the speed of plant growth in tomatoes (Flowering and fruiting). In addition, there was no interaction between bacterial inoculation and biochar application on the parameters studied. The bacterial inoculation did not significantly affect any parameters studies. This is contrasted by the results from the treatments with biochar application which showed the enhancement of plant growth and yield. The sustainability of the bacterial strains used are suggested to be tested before starting the experiment.